ICHAMPSS: Usability and Psychosocial Impact for Increasing Implementation of Sexual Health Education. Issue 3 (May 2017) - Hernandez, Belinda F.; Peskin, Melissa F.; Shegog, Ross; Gabay, Efrat K.; Cuccaro, Paula M.; Addy, Robert C.; Ratliff, Eric; Emery, Susan T.; Markham, Christine M.
Introduction . Diffusion of sexual health evidence-based programs (EBPs) in schools is a complex and challenging process. iCHAMPSS ( CH oosing A nd M aintaining effective P rograms for S ex education in Schools) is an innovative theory- and Web-based decision support system that may help facilitate this process. The purpose of this study was to pilot-test iCHAMPSS for usability and short-term psychosocial impact. Method . School district stakeholders from across Texas were recruited ( N = 16) and given access to iCHAMPSS for 3 weeks in fall 2014. Pre- and posttests were administered to measure usability parameters and short-term psychosocial outcomes. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results . Most participants reported that iCHAMPSS was easy to use, credible, helpful, and of sufficient motivational appeal. iCHAMPSS significantly increased participants' self-efficacy to obtain approval from their board of trustees to implement a sexual health EBP. Positive, though nonsignificant, trends included increased knowledge to locate EBPs, skills to prioritize sexual health education at the district level, and ability to choose an EBP that best meets district needs. Conclusions . iCHAMPSS is an innovative decision support system that could accelerate uptake of EBPs by facilitating diffusion and advance the field of dissemination and implementation science for the promotion of sexual health EBPs.